Effect of Excessive Screen Time on Cardiorespiratory Fitness in Children: A Longitudinal Study - Ryo Goto; Tsunenori Isa; Rika Kawaharada; Kana Horibe; Yamato Tsuboi; Kiyomasa Nakatsuka; Kazuaki Uchida; Kenta Saeki; Rei Ono (MDPI AG, 2022)
Background: This study investigated the effect of different components of screen time (mobile phone use, TV/video viewing, and video gaming) on cardiorespiratory fitness (CRF) development in children aged 9-12 years. Methods: This was a two-year longitudinal study conducted with 175 children (49.7% girls, mean age = 9.5) in Japan. CRF was assessed using a 20 m shuttle run test conducted at baseline and again at follow-up. Children were categorized as "Good" or "Poor" based on the change in CRF scores for each gender. Screen time was assessed using a self-reported questionnaire at baseline and termed as "high" if children reported ≥ 2 h/day. Univariate and multivariate logistic regression analyses were performed after adjusting for gender, physical activity, and time of data collection. Results: Children scoring "high" on mobile phone use had lower odds of being categorized as "Good" in CRF change (crude odds ratio (OR): 0.34; 95% confidence interval (CI): 0.15-0.90 (adjusted OR: 0.33; 95% CI: 0.12-0.91)). There were no significant effects of TV/video viewing (crude OR: 1.54; 95% CI: 0.84-2.81) and video gaming (crude OR: 0.98; 95% CI: 0.48-1.97) on changes in CRF. Conclusions: Limiting excessive mobile phone usage might be important for ensuring healthy development of CRF in children.